The risks of prescription drugs - Light, Donald, Jr., 1942- (Columbia University Press and Social Science Research Council series on the privatization of risk., 2010)
Few people realize that prescription drugs have become a leading cause of death, disease, and disability. Adverse reactions to widely used drugs, such as psychotropics and birth control pills, as well as biologicals, result in FDA warnings against adverse reactions.The Risks of Prescription Drugs describes how most drugs approved by the FDA are under-tested for adverse drug reactions, yet offer few new benefits. Drugs cause more than 2.2 million hospitalizations and 110,000 hospital-based deaths a year. Serious drug reactions at home or in nursing homes would significantly raise the total. Women, older people, and people with disabilities are least used in clinical trials and most affected.Health policy experts Donald Light, Howard Brody, Peter Conrad, Allan Horwitz, and Cheryl Stults describe how current regulations reward drug companies to expand clinical risks and create new diseases so millions of patients are exposed to unnecessary risks, especially women and the elderly. They reward developing marginally better drugs rather than discovering breakthrough, life-saving drugs. The Risks of Prescription Drugs tackles critical questions about the pharmaceutical industry and the privatization of risk. To what extent does the FDA protect the public from serious side effects and disasters? What is the effect of giving the private sector and markets a greater role and reducing public oversight? This volume considers whether current rules and incentives put patients' health at greater risk, the effect of the expansion of disease categories, the industry's justification of high U.S. prices, and the underlying shifts in the burden of risk borne by individuals in the world of pharmaceuticals. Chapters cover risks of statins for high cholesterol, SSRI drugs for depression and anxiety, and hormone replacement therapy for menopause. A final chapter outlines six changes to make drugs safer and more effective.Suitable for courses on h.